TAHAPAN DAN KERANGKA MANAJEMEN PERENCANAAN DALAM PERSPEKTIF AL-QURAN - Alfisyah (PT. Hasba Edukasi Mandiri, 2025)
Planning is a core managerial function that determines the direction, effectiveness, and efficiency of organizational goal attainment. From an Islamic perspective, planning extends beyond technical and rational considerations to incorporate spiritual values derived from the Qur’an. This article examines the stages, framework, and ethical principles of management planning from a Qur’anic perspective and explores their implications for managerial practice, particularly in Islamic education. This study adopts a qualitative approach through library research, analyzing relevant Qur’anic verses, hadith, and scholarly literature. The findings reveal that Islamic planning comprises several key stages, including goal formulation, program and strategy development, continuous evaluation and improvement, and systematic financial planning. The Qur’anic planning framework emphasizes sincere intention (ikhlas), optimal effort (ikhtiar), reliance on Allah (tawakkal), self-reflection (muhasabah), and a balanced orientation toward worldly and hereafter objectives. Moreover, Islamic planning ethics highlight the necessity of aligning human plans with divine will, exercising tawakkul after exerting maximum effort, and accepting outcomes with contentment toward divine decree (qadha and qadar). Overall, management planning grounded in the Qur’anic perspective offers a holistic model that integrates rational, ethical, and spiritual dimensions to achieve sustainable and value-based success in both worldly and eschatological contexts.